Dialética do trabalho. Sobre o Hegel de Adorno - Zanotti, Giovanni (Revista Eletrônica Estudos Hegelianos, 2020)
This article investigates Adorno’s interpretation of the Hegelian dialectic as is developed in his Hegel: Three Studies(1963), in its connection with the philosophical problem of labor. If, on the one side, Adorno’s entire argumentation is directed at refuting some of the traditional commonplaces about Hegel’s “subjectivism”, on the other side he seems to claim that, in some sense, these same allegations also have a point. However, Adorno’s strategy is different from that of undialectical critics of Hegel – including the Hegelian Left and, to some extent, the young Marx – inasmuch as he recognizes the progressive content of Hegel’s idealism itself. The fact that such idealism is at the same time criticized is due to Adorno’s core idea of the duplicity oflabor as an inseparable unity of freedom and unfreedom. Hegel’s truth relies, according to him, on the vindication of labor’s possibilities, while his falsity consists in its ontologization. In the conclusion, it is suggested that, for Adorno, the duplicity of labor grounds an analogous duplicity of dialectic itself, which should not be considered as an ontology, but as the theoretical expression of a transient reality.